Workers’ Behavioral Practices on the Eve of February, 1917: On the Prerequisites for the Revolution - Olga Sergeevna Porshneva (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2017)
This article considers the role of the workers’ movement, mass sentiments, and behavioral practices of workers in the development and resolution of the revolutionary crisis on the eve of February, 1917 in the context of the modern historiographical situation. The author analyses the main factors and manifestations of the aggravation of workers’ protest moods and protest activity between mid-1915 and early 1917. It is established that the most urbanised strata of workers, primarily the metalworkers of Petrograd played a major role in the development of the political strike movement. The worsening of the socio-economic situation and the growth of protest activity of the mass strata of workers correlated. The labour movement also depended on the crisis of the upper strata more than on the agitation of revolutionary parties. The author maintains that the workers’ protest practices, which received an impulse in the autumn of 1916, were based on their idea of the need for a radical democratisation of the political system, the abolition of the autocratic regime, which became widespread in the working environment. While it was not the workers that played a decisive role in overthrowing autocracy in February 1917, the author cautions against the underestimation of the role of workers as one of the main social actors of the Revolution. The soil for the overthrow of autocracy ripened in the mass sentiments of workers, their spontaneous movement, which the left parties rested on. Without the high activity of workers, the February events would not have become a popular movement.